Obituary: Kazimierz Bielenin (29 January 1923 - 19 November 2011) - Szymon Orzechowski (EXARC Journal)
On the 19th of November 2011, Prof. dr hab. Kazimierz Bielenin died in Kraków after a long and exhausting illness. He was a great scientist and scholar but also a very modest man with a great personality. He was born on the 29th of January 1923 in Brzeszcze near Oświęcim. He completed his university studies at the Jagiellonian University in Kraków and took the first steps of his professional career at the Nicolaus Copernicus University in Torun.